THE EFFICACY OF WRITTEN CORRECTIVE FEEDBACK IN IMPROVING ENGLISH FOREIGN LANGUAGE UNIVERSITY STUDENTS’ WRITING - Febrian, Revo Aditama; Nurcholis, Ivan Achmad (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study investigates the efficacy of written corrective feedback (WCF) in enhancing the writing skills of university students learning English as a Foreign Language (EFL). The study aims to determine the overall effectiveness of WCF, identify the most beneficial types, and explore students' perceptions and attitudes towards receiving WCF. Existing research predominantly focuses on short-term impacts, neglecting long-term effects and individual differences such as learning styles and motivation, particularly in non-Western educational settings. Addressing these gaps could lead to more effective and personalized feedback strategies. The study employs a survey design to collect data from sixth-semester students in the Scientific Writing class at Muhammadiyah University of Bengkulu. Participants were selected using purposive sampling. The questionnaire, developed through a thorough literature review and expert consultations, was divided into five sections to ensure comprehensiveness and relevance. The findings indicate that students perceive WCF as effective in improving various aspects of their writing skills, particularly appreciating clear and specific feedback. Despite some challenges such as variability in feedback frequency and individual differences, students reported high satisfaction with the detailed and constructive nature of the feedback. The study concludes that WCF significantly enhances EFL students' writing proficiency, emphasizing the importance of personalized, timely, and accessible feedback. Future research should explore the long-term effects of WCF and the potential of technology in delivering effective feedback.